Motives for using news podcasts and political participation intention in South Korea: The mediating effect of political discussion. Issue 1 (May 2023) - Cho, Yoon Y.; Park, Ahran; Choi, Jinho
The purpose of this study is to examine Korean listeners' motivations for listening to political news podcasts drawing on uses and gratifications. This study revealed five motivations: social support, convenience, ease of obtaining political information, diversion/habitual use, and alternative use/de-authoritative flow. The study also confirmed that the extent to which gratifications sought for political news podcasts differs depending on listeners' political orientations. Liberals have stronger motivations for convenience in use, ease of obtaining political information, and diversion/habitual use compared to conservatives. Furthermore, this research found that the motivations for social support, alternative use, and diversion/habitual use tend to impact political discussions with others, both online and offline, and this process could encourage their intention of political participation as well.